2023
DOI: 10.3389/fpls.2023.1183144
|View full text |Cite
|
Sign up to set email alerts
|

P3/P3N-PIPO of PVY interacting with BI-1 inhibits the degradation of NIb by ATG6 to facilitate virus replication in N. benthamiana

Abstract: IntroductionAutophagy not only plays an antiviral role but also can be utilized by viruses to facilitate virus infection. However, the underlying mechanism of potato virus Y (PVY) infection against plant autophagy remains unclear. BI-1, localizing to the endoplasmic reticulum (ER), is a multifunctional protein and may affect the virus infection.MethodsIn this study, Y2H, BiFC, qRT-PCR, RNA-Seq, WB and so on were used for research.ResultsP3 and P3N-PIPO of PVY can interact with the Bax inhibitor 1 (BI-1) of N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…The P22 protein of ToCV interacts with the N. benthamiana B-cell lymphoma2-associated athanogenes5 (NbBAG5), an evolutionarily conserved protein mainly involved in plant growth and stress response, and induces NbBAG5 expression, leading to the inhibition of autophagy and favoring viral infection [ 74 ]. Another report revealed that the interaction of P3 and/or P3N-PIPO of PVY with BI-1 decreases the expression of the ATG6, thereby inhibiting the autophagic degradation of viral NIb and enhancing viral replication [ 75 ]. Thirdly, viruses can induce specific structures to prevent viral protein association with autophagosomes.…”
Section: Autophagy–virus Interplay In Plants: From Antiviral Recognit...mentioning
confidence: 99%
“…The P22 protein of ToCV interacts with the N. benthamiana B-cell lymphoma2-associated athanogenes5 (NbBAG5), an evolutionarily conserved protein mainly involved in plant growth and stress response, and induces NbBAG5 expression, leading to the inhibition of autophagy and favoring viral infection [ 74 ]. Another report revealed that the interaction of P3 and/or P3N-PIPO of PVY with BI-1 decreases the expression of the ATG6, thereby inhibiting the autophagic degradation of viral NIb and enhancing viral replication [ 75 ]. Thirdly, viruses can induce specific structures to prevent viral protein association with autophagosomes.…”
Section: Autophagy–virus Interplay In Plants: From Antiviral Recognit...mentioning
confidence: 99%